THE ADVANTAGE OF VIDEO MATERIALS IN TEACHING ENGLISH TO SCHOOLCHILDREN - Xаlikоvа, Latofat (Журнал иностранных языков и лингвистики, 2023)
The article presents a hypothetical investigation into the desirability of an English teacher using video materials to improve the communication skills of younger students. It was found that for teaching communicative and socio-cultural competence in English it is not enough to use the methods shown in the teaching program and to achieve a quality result, the use of additional learning strategies, including video materials, is essential. One of the most important is the British Board for Kids - a body created by the British Chamber. The stage highlights numerous free online games, tunes, stories, and entertainment for children. Communicative competence includes the following components: linguistic, phonetic, sociolinguistic, digressive, and sociocultural. The use of video material as an additional instrument of FL teaching opens up wide openings for dynamic work in the context of shaping discourse skills and abilities as well as socio-cultural competence.